2017
DOI: 10.1177/0192636517712450
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Common Core State Standards Implementation: Views From Six States

Abstract: The implementation of the Common Core State Standards has posed a number of challenges for school leaders. This study applies a policy implementation conceptual framework to analyze data gathered from 46 interviews in six states. Findings suggest the existence of multiple barriers to Common Core State Standards implementation. To promote implementation, states need to increase local capacity, build will to implement, and engage in information campaigns that promote the Common Core beyond an audience of educato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This nationalization of EL accountability policy stands in stark contrast to the decline in overall specificity around general education accountability, beginning with NCLB waivers and concluding with state ESSA plans, which were uniformly approved without much critical review following political pushback (Author, 2019a). It is also notable that in the context where CCSS-aligned national assessment consortia have struggled to maintain stable relationships with states due to political backlash (Smith & Thier, 2017), WIDA's and ELPA21's standards and assessments have remained relatively stable with most states utilizing the same ELP standards and assessments with little concern about if and how reliance on these national consortia undermines local control.…”
Section: The Nationalization Of Elp Assessmentsmentioning
confidence: 99%
“…This nationalization of EL accountability policy stands in stark contrast to the decline in overall specificity around general education accountability, beginning with NCLB waivers and concluding with state ESSA plans, which were uniformly approved without much critical review following political pushback (Author, 2019a). It is also notable that in the context where CCSS-aligned national assessment consortia have struggled to maintain stable relationships with states due to political backlash (Smith & Thier, 2017), WIDA's and ELPA21's standards and assessments have remained relatively stable with most states utilizing the same ELP standards and assessments with little concern about if and how reliance on these national consortia undermines local control.…”
Section: The Nationalization Of Elp Assessmentsmentioning
confidence: 99%
“…Districts also have varied in terms of the curricula and instructional materials they have made available and the ease with which teachers have been able to access and implement the materials coherently (Gao et al, 2018; Makkonen & Sheffield, 2016; Porter et al, 2014; Smith & Thier, 2017; Swars & Chestnutt, 2016; Timar & Carter, 2017). Providing high-quality science materials has been especially challenging for districts.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The issue of capacity is reflected in more recent scholarship as well. Smith and Thier (2017) found that SEA officials felt that they lacked the capacity themselves to take on the increasing number of responsibilities that ESSA allocated to states compared with previous federal requirements—for example, states now have more control over their accountability indicators and their interventions for low performing schools. This observation is reflected in the Rentner, Frizzell, and Kober (2017) study where 31 out of 45 states reported needing to work more collaboratively with districts, or let districts take the lead in supporting school improvement, because SEAs did not have the capacity to take on that workload.…”
mentioning
confidence: 99%